THE FORMATION OF PHRASEOLOGICAL UNITS WITH SOMATIC WORDS IN LANGUAGES (Scientific journal of the Fergana State University, 2023)
The article discusses the formation of phraseological units with the participation of somatic words in different languages, the definition of somatisms in different languages, changes in the vocabulary of the language, which are currently being discussed in German, Uzbek and Russian languages.